Global epidemiology of cancer : diagnosis and treatment - Moini, Jahangir, 1942-; Avgeropoulos, Nicholas G.; Badolato, Craig (Hoboken, NJ : John Wiley & Sons, Inc., 2022)
"The authors welcome you to this first edition of "Global Epidemiology of Cancer (Diagnosis and Treatment)". Since cancer is a leading cause of death globally and the second highest cause of death in the United States, our goals are to discuss the global epidemiology of cancer, with detailed focus on diagnosis and treatment. The book will meet the needs of readers by providing solid information about epidemiology, etiology, risk factors, pathophysiology, clinical manifestations, diagnosis, treatment, prevention, early detection, and prognosis. It has been written to provide logical, step-by-step information on a large variety of cancers in different organs. The chapters are formatted to include keywords, significant points, clinical cases with questions and answers, key terms, and references. Tables summarize information into easy-to-remember topics throughout the chapters. The book is organized into three parts that contain a total of 18 chapters. It is designed for graduate and postgraduate students that include medical students; residents in internal medicine and oncology; nurses, nurse practitioners, and physician assistants"--
BIBINDX
Keywords: Neoplasms -- epidemiology; Epidemiologic Methods; Neoplasms -- etiology; Global Health; Electronic books